Tingkat Keterbacaan (Readibility) Informasi Keuangan pada Media Publik Bank BTN dan Dampaknya terhadap Pemahaman Nasabah - Meilina Widya Dali; Ariel Setiawan Kum; Nurlaila Hilali; Nurwidyawati Nonoi; Faldi Husna; Nurhujah Syahrani Entengo; Nurmila Febriani Pakaya; Nur Asizah; Jamal Rasidi Saman; Amelia Defriana B. Kumisi; Fitri Febrianti Muchtar; Aurel Septian Kurniawan; Nur Marfa Kusira; Aisyarah Arabella Piuwa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Financial information presented through bank public media plays a crucial role in helping customers understand the financial conditions and services offered. However, the readability of this information is often hampered by the use of technical terms and less straightforward language. This study aims to analyze the readability of financial information in Bank BTN's public media and its impact on customer understanding. The research method used is a qualitative descriptive approach, with data collection techniques through observations of Bank BTN's public media and customer interviews. The results indicate that the readability of Bank BTN's financial information is in the adequate category, but some sections are still difficult for customers to understand, especially those without a financial background. This low readability impacts customers' suboptimal understanding of the financial information provided. Therefore, Bank BTN is advised to simplify the language and presentation of information to make it more easily understood by all levels of customers.